Assessment of patient’s compliance in taking ophthalmology drugs at the Out-Patient Pharmacy, Hospital Batu Pahat - Khalid, Muhamad Shukry; Mudasir, Khairani (2011)
Patient’s compliance refers to the willingness and ability of an individual to follow health-related advice, to take medication as prescribed, to attend scheduled clinic appointments and to complete recommended investigations. It is a major health issue, with outcomes related to levels of morbidity, mortality and cost utilization. Poor compliance has been reported as the most common cause of non-response to medication, with evidence to show that patients who adhere to treatment recommendations have better health outcomes than those who do not adhere, even when taking a placebo. Evidence-based practice guidelines, founded on clinical, behavioral and educational concepts, provide a means of measuring outcomes related to health status, patient satisfaction and cost-benefit issues, and may help to ensure that responsibility for compliance is shared between the clinician and the patient. An investigation into the patient’s compliance using eye drops has been done by using survey and questionnaire. Patients were asked with a few simple questions regarding to the Morisky Scale. To score the Morisky Scale, each question answered with a NO receives a score of 1. The possible scoring range is therefore 0 to 4. Patients with higher scores are at greater risk for non-adherent behavior. Patients with lower scores predicted to be more adherent to prescribed medication therapies. Morisky Scale consists of 4 categories. There are compliant, satisfactory, average and poor. The results are 23.36% is compliant, 16.83% is satisfactory, 36.45% is average and 13.08% is poor. There are many reasons why patients are non-compliant. The reasons are the side effects of the drugs, forget to use the eye drops, do not understand about their diseases and medications given, their major life events make them to focus away from using their medications and a lack of comprehension between patient and the health practitioner.